PREDICTION OF PARTICLE COLLECTION EFFICIENCY, THE POROSITY AND THE PRESSURE DROP ACROSS FILTRATION MEDIA USING FEMLAB - MOHD ZAINURI, ZAININA DINI (universiti teknologi petronas, 2005)
This report consists of a research project on the prediction of particle collection efficiency, the porosity and the pressure drop across filtration media at stationary phase. Two types ofmodel were compared in this project. The first one is the model developed by Awni Y. Al-Otoom, which simulates particle distribution on the filter cloth and predicts whether each particle was trapped on or escapes the filter cloth. The filtration parameters will becalculated by the number ofparticles trapped and the geometry ofthe cake simulated on the filter cloth. The second model is developed based on flow through porous media using Darcy's Law and FEMLAB software. In this model, the pressure drop will be simulated using the software and other parameters will be calculated from it. From the project, it can be concluded that the pressure drop shown by both models agree with thetheory. This result was the same for porosity and efficiency predicted by Al-Otoom. However, the FEMLAB model needs more experimental information as the porosity prediction is only applicable to the filter cloth porosity, while efficiency prediction requires the pressure drop contributed solely by the filter cake.